Neuroendocrine host factors and inflammatory disease susceptibility. - Ligier, S (1999)
The etiology of autoimmune diseases is multifactorial, resulting from a combination of genetically predetermined host characteristics and environmental exposures. As the term autoimmune implies, immune dysfunction and dysregulated self-tolerance are key elements in the pathophysiology of all these diseases. The neuroendocrine and sympathetic nervous systems are increasingly recognized as modulators of the immune response at the levels of both early inflammation and specific immunity. As such, alterations in their response represent a potential mechanism by which pathologic autoimmunity may develop. Animal models of autoimmune diseases show pre-existing changes in neuroendocrine responses to a variety of stimuli, and both animal and human studies have shown altered stress responses in the setting of active immune activation. The potential role of the neuroendocrine system in linking environmental exposures and autoimmune diseases is 2-fold. First, it may represent a direct target for toxic compounds. Second, its inadequate function may result in the inappropriate response of the immune system to an environmental agent with immunogenic properties. This article reviews the relationship between autoimmune diseases and the neuroendocrine system and discusses the difficulties and pitfalls of investigating a physiologic response that is sensitive to such a multiplicity of environmental exposures.